Moderate Sun Exposure Is the Complementor in Insufficient Vitamin D Consumers - Wu, Shou-En; Chen, Wei-Liang (Frontiers in Nutrition, 2022)
Background & Aims: Vitamin (Vit) D plays a vital role in human health, and prevalence of Vit D deficiency worldwide has been a rising concern. The current study investigates the serum 25-hydroxy-Vit D (25(OH)D) status in healthy U.S. civilians, and identifies how the two main sources, sun exposure and dietary Vit D intake, determine the final 25(OH)D levels in individuals. Methods: 2360 of participants from The National Health and Nutrition Examination Survey (NHANES) 2009-2014 were analyzed. We divided the levels of sun exposure and dietary Vit D intake of all subjects into 10 strata and gave a score ranging from 1 to 10 points, respectively. Scores 1-5 in sun exposure and dietary intake were considered as relatively low exposure groups, whereas scores 6-10 were considered as relatively high exposure groups. Serum Vit D inadequacy was defined as <50 nmol/L. Linear and logistic regression analyses were used to examine the associations between sources of Vit D and serum 25(OH)D levels. Results: In relatively low Vit D intake groups (Vit D intake score 1 to 5), relatively high sun exposure (sun exposure score > 5) resulted in higher serum 25(OH)D levels (average 57 nmol/L) compared with relatively low sun exposure (sun exposure score < 5) (average 50 nmol/L), whereas this difference became negligible in high intake groups (Vit D intake score 6 to 10). Moreover, the greatest slope occurred in the low Vit D intake curve (Decile 3 of Vit D intake), showing increased sun exposure time causing the greatest degree of change in serum 25(OH)D level in this group. Conclusions: Sun exposure can significantly make up for deficiencies in subjects who consume insufficient dietary Vit D. Compared with the extra cost and time for building habits of Vit D supplementation, moderate sun exposure appears to be a simple and costless means for the public to start in daily practice.